Composting process evaluation of two mixtures of poultry manures - Riera, Nicolas I.; Della Torre, Virginia; Rizzo, Pedro F.; Butti, Mariano; Bressan, Fabiana M.; Zarate, Natalia; Weigandt, Cristian; Crespo, Diana E. C. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Chicken production wastes, principally poultry manure (layers) and litter (from chickens for fattening), may impact negatively on the environment, contributing to soil, water and air pollution. Aerobic stabilization through composting is an alternative to reduce contamination. This study aims to evaluate the composting process in two mixtures with different percentages of poultry manure of laying chickens and broiler poultry litter. Two mixtures were composted containing 81% and 70% of poultry wastes for 16 weeks. The analytical parameters were: temperature (T°), pH, electrical conductivity (EC), humidity (H), cationic exchange capacity (CEC), total organic carbon (TOC), amonium (NH4+), nitrate (NO3- ), total nitrogen (TN), soluble carbon soluble (SC) were determined in each treatment. The final compost A and B characteristics were 7,1 - 6,8, CE 3,3 - 2,9 (mS.cm-1), COT 14,8 - 17,9%, NT 0.97 - 0.88%, NH4+ 501 - 144,9 mg kg-1, NO3 - 552,3 -543,0 mg kg-1 respectively. The composting process may be a tool to stabilize poultry wastes, minimizing its environmental damage.